FAKTOR – FAKTOR YANG MEMENGARUHI STOCK RETURN PADA PERUSAHAAN MANUFAKTUR - Sumarwan, Styven James; Chandra, Santoso (E-Jurnal Akuntansi TSM, 2024)
The purpose of this reseach is to provide knowledge that helps investors in determining companies to invest their capital in the form of shares on the Indonesian Stock Exchange. This study also uses calculations in the form of firm size, profitability, liquidity, market, operating cash flow, investing cash flow, financing cash flow, and debt policy so that investors can find out various things the company does in its development. This can be seen from the financial statements that aim to determine investors choices for the company. This research data consists of financial ratios from the financial statements of manufacturing companies for 3 years 2018 to 2020. This study discusses 8 independent variables and also uses a purposive sampling model that is used for sampling and uses 66 companies and a total of 158 company data. Researchers used five sample selection criteria and used multiple regression analysis methods. The results of this indicate that firm size has a negative effect on stock returns, while profitability, liquidity, market, operating cash flow, investing cash flow, financing cash flow and debt policy have no effect on stock returns. Abstract: The purpose of this reseach is to provide knowledge that helps investors in determining companies to invest their capital in the form of shares on the Indonesian Stock Exchange. This study also uses calculations in the form of firm size, profitability, liquidity, market, operating cash flow, investing cash flow, financing cash flow, and debt policy so that investors can find out various things the company does in its development. This can be seen from the financial statements that aim to determine investors choices for the company. This research data consists of financial ratios from the financial statements of manufacturing companies for 3 years 2018 to 2020. This study discusses 8 independent variables and also uses a purposive sampling model that is used for sampling and uses 66 companies and a total of 158 company data. Researchers used five sample selection criteria and used multiple regression analysis methods. The results of this indicate that firm size has a negative effect on stock returns, while profitability, liquidity, market, operating cash flow, investing cash flow, financing cash flow and debt policy have no effect on stock returns. Abstract: The purpose of this reseach is to provide knowledge that helps investors in determining companies to invest their capital in the form of shares on the Indonesian Stock Exchange. This study also uses calculations in the form of firm size, profitability, liquidity, market, operating cash flow, investing cash flow, financing cash flow, and debt policy so that investors can find out various things the company does in its development. This can be seen from the financial statements that aim to determine investors choices for the company. This research data consists of financial ratios from the financial statements of manufacturing companies for 3 years 2018 to 2020. This study discusses 8 independent variables and also uses a purposive sampling model that is used for sampling and uses 66 companies and a total of 158 company data. Researchers used five sample selection criteria and used multiple regression analysis methods. The results of this indicate that firm size has a negative effect on stock returns, while profitability, liquidity, market, operating cash flow, investing cash flow, financing cash flow and debt policy have no effect on stock returns.